Study of Construction Vehicles Automatic Transmission Wear Degree Based on Spectroscopic Technology - Lidan Chen (Institute of Advanced Engineering and Science, 2012)
Flame atomic absorption spectrometry (FAAS) was adopted to detect the construction vehicles automatic transmission through simultaneous determination of typical metal elements contents (Copper, Chromium and Iron) in automatic transmission fluid (ATF). Standard curves of Copper, Chromium and Iron were portrayed. Six parallel tests were implemented and the relative standard deviations (RSD) were 2.59%, 2.89% and 2.71% for Copper, Chromium and Iron separately. Additionally, under the same test conditions and analysis methods, contents of Copper, Chromium and Iron in different mileages of construction vehicles automatic transmission were tested. Analysis showed that, with the increase of mileage, the wear degree of construction vehicles automatic transmission increased and the contents of Copper, Chromium and Iron in ATF were also increased follow specific functions for each element under certain driving condition, and the correlation coefficients R were 0.9994, 0.9993 and 0.9997 correspondingly. Finally, results illustrated that FAAS could serve as the rapid and non-destructive method to determine the contents of Copper, Chromium and Iron, and further to achieve the goal of examining the conditions of the major components of automatic transmission. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.853